2017
DOI: 10.1108/edi-01-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

News media and the racialization of protest: an analysis of Black Lives Matter articles

Abstract: Purpose The purpose of this paper is to examine coverage of the Black Lives Matter (BLM) movement in seven US-based newspapers to determine whether the protest paradigm, “a pattern of news coverage that expresses disapproval toward protests and dissent,” and other marginalizing techniques are present, and racialized. Design/methodology/approach Relevant articles published during a six-month period of 2014 near the death of Michael Brown were retrieved from the selected outlets, including the New York Times, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 33 publications
1
67
0
Order By: Relevance
“…We caution against this interpretation, given that Black Lives Matter is ultimately a movement in its early stages and its primary focus still seems to be on online organization, which may in turn have an indirect effect on increasing the coverage of incidents of police brutality (Freelon et al, 2018). We and other scholars (Byrd et al, 2017;Cox, 2017;Leopold & Bell, 2017;Mundt, Ross, & Burnett, 2018) have approached Black Lives Matter as a social movement, but the disparate and loosely knit nature of the organization may classify it as a different type of movement altogether, and perhaps one that requires different measures of success. Still, our research suggests that more work needs to be done and that, at the current date, Black lives do not matter enough.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…We caution against this interpretation, given that Black Lives Matter is ultimately a movement in its early stages and its primary focus still seems to be on online organization, which may in turn have an indirect effect on increasing the coverage of incidents of police brutality (Freelon et al, 2018). We and other scholars (Byrd et al, 2017;Cox, 2017;Leopold & Bell, 2017;Mundt, Ross, & Burnett, 2018) have approached Black Lives Matter as a social movement, but the disparate and loosely knit nature of the organization may classify it as a different type of movement altogether, and perhaps one that requires different measures of success. Still, our research suggests that more work needs to be done and that, at the current date, Black lives do not matter enough.…”
Section: Discussionmentioning
confidence: 89%
“…Further, the fact that the only spike in news coverage of and Internet searches for the movement occurred following a negative event supports much of what we know regarding racialized patterns of news coverage. Regarding the Black Lives Matter movement specifically, Leopold and Bell (2017) have previously shown that much of the mainstream coverage of the movement is negative, and research on the Civil Rights Movement demonstrated that media coverage became more and more negative over time (Bond, 2001). We consider these findings to be supportive of the argument of Van Dijk (2015) that the routinized structure of modern news places an emphasis on stories that are attentiongrabbing, fast to produce, and sensational, and that this process ultimately reproduces systemic racial bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations